High‐intensity non‐invasive ventilation in stable hypercapnic COPD: Evidence of efficacy and practical advice. Issue 4 (30th November 2018) - van der Leest, Sietske; Duiverman, Marieke L.
ABSTRACT: Patients with end‐stage chronic obstructive pulmonary disease (COPD) frequently develop chronic hypercapnic respiratory failure (CHRF), with disabling symptoms and poor survival. The use of long‐term nocturnal non‐invasive ventilation (NIV) to treat CHRF in COPD has long been subject of debate due to conflicting evidence. However, since the introduction of high‐intensity NIV (HI‐NIV) in COPD, physiological and clinical benefits have been shown. HI‐NIV refers to specific ventilator settings used for NIV aimed at achieving normocapnia or the lowest partial arterial carbon dioxide pressure (PaCO2 ) values as possible. This review will provide an overview of existing evidence of the efficacy of HI‐NIV stable COPD patients with CHRF. Secondly, we will discuss hypotheses underlying NIV benefit in stable hypercapnic COPD, providing insight into better patient selection and hopefully more individually titrated HI‐NIV. Finally, we will provide practical advice on how to initiate and follow‐up patients on HI‐NIV, with special emphasis on monitoring that should be available during the initiation and follow‐up of HI‐NIV, and will discuss more extended monitoring techniques that could improve HI‐NIV treatment in the future.